2004
DOI: 10.1111/j.1420-9101.2004.00737.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex-ratio distorter of Drosophila simulans reduces male productivity and sperm competition ability

Abstract: The aim of the present study was to determine whether the effects of sex‐ratio segregation distorters on the fertility of male Drosophila simulans can explain the contrasting success of these X‐linked meiotic drivers in different populations of the species. We compared the fertility of sex‐ratio and wild‐type males under different mating conditions. Both types were found to be equally fertile when mating was allowed, with two females per male, during the whole period of egg laying. By contrast sex‐ratio males … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 40 publications
4
69
2
Order By: Relevance
“…This could lead to selection for polyandry in species manipulated by CI-inducing Wolbachia. This theory is also applicable to other SGEs that affect sperm production, such as sex-linked meiotic driver genes (Wilkinson & Fry 2001;Atlan et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could lead to selection for polyandry in species manipulated by CI-inducing Wolbachia. This theory is also applicable to other SGEs that affect sperm production, such as sex-linked meiotic driver genes (Wilkinson & Fry 2001;Atlan et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the ejaculates of infected and uninfected males are likely to compete in the wild and could decrease the rate of CI induction. Decreasing the rate of CI induction as a consequence of sperm competition, undermines the advantage to infected females and therefore slows the spread of Wolbachia (Champion de Crespigny et al 2005). The rate of spread of Wolbachia may be strongly linked to the successful maintenance of the infection, since Wolbachia is thought to be vulnerable at low frequency due to stochastic environmental conditions (Champion de Crespigny et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Accessory gland expression is downregulated in the resistant Y males Sex-ratio males are not only weaker in sperm displacement but are also discriminated against by non-virgin females in both Drosophila pseudoobscura and D. simulans (Wu, 1983a, b;Atlan et al, 2004). Males with the Winters sex-ratio also show reduced fertility (Tao et al, 2007b).…”
Section: T E S T I S a C C E S S O R Y G L A N D F A T B O D Y C R O mentioning
confidence: 99%
“…This could explain the seasonal fluctuations of SR as do the seasonal fluctuations of SR that are observed in D. pseudoobscura (Bryant et al 1982). The negative effect of multiple mating on the fertility of SR males has been well documented in laboratory conditions (e.g., Hickey and Craig 1966;Wu 1983c;Jaenike 1996;Atlan et al 2004;Wilkinson et al 2006), and the effect of density on SR frequency has been observed in experimental populations of D. pseudoobscura (Beckenbach 1983). In addition, as for many other selfish genetic elements (Price and Wedell 2008), SR males are usually poor sperm (or pollen) competitors against standard males (e.g., Wu 1983b; Taylor et al 1999;Wilkinson and Sanchez 2001;Wilkinson et al 2006;Angelard et al 2008;Price et al 2008b).…”
Section: Maintenance Of Polymorphismmentioning
confidence: 85%
“…When the proportion of females increases in the population because of the driver, the male mating rate increases and standard males are favored because they sire proportionally more offspring relative to their transferred sperm. Variation in population density can influence the male mating rate and contribute to the differences in SR abundance (Beckenbach 1978;Atlan et al 2004). This could explain the seasonal fluctuations of SR as do the seasonal fluctuations of SR that are observed in D. pseudoobscura (Bryant et al 1982).…”
Section: Maintenance Of Polymorphismmentioning
confidence: 99%